2003
DOI: 10.1021/jp0302865
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on the Relationship between Nucleophilicity and Ionization Potentials in Solution Phase

Abstract: In this paper we describe a method to obtain estimates of the relative nucleophilicity for a series of neutral and charged electron donors from their solution phase ionization potential (I s ). The relationship between nucleophilicity and the solution phase ionization potentials is first tested for experimental I s values in aqueous solution. On the basis of the meaningful relationship found, the method is then applied to the theoretical solution phase I s obtained at the IPCM-MP2/6-311G(2d,p) level of theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 28 publications
1
90
0
Order By: Relevance
“…A linear correlation with the E T (30) scale of solvent polarity is indicative of Figure 3 indicated that the transition is accompanied by a decrease in the dipole moment for the nitrone N1, as is also true for the indicator dye of the E T (30) scale. The poorer sensitivity of E(F) compared to E(A) towards change in the solvent polarity was observed.…”
Section: Photophysical Study/solvent Interactionmentioning
confidence: 58%
See 1 more Smart Citation
“…A linear correlation with the E T (30) scale of solvent polarity is indicative of Figure 3 indicated that the transition is accompanied by a decrease in the dipole moment for the nitrone N1, as is also true for the indicator dye of the E T (30) scale. The poorer sensitivity of E(F) compared to E(A) towards change in the solvent polarity was observed.…”
Section: Photophysical Study/solvent Interactionmentioning
confidence: 58%
“…The present paper reports the trend of forming charge transfer complexes by the nitrone (N1) with the unsaturated ketones (K1 -K3) in terms of experimental transition dipole strengths, resonance energies and formation constants of the complexes in non-polar toluene medium. Experimental findings of the trend in non-covalent interaction were well substantiated theoretically with the help of DFT calculated electrophilicity and nucleophilicity indices [23,24,[28][29][30] as well as in terms of frontier molecular orbital energies [24].…”
Section: Introductionmentioning
confidence: 65%
“…To describe the nucleophilicity N F D of a molecule we adopted the method proposed by Contreras et al [18], where …”
Section: Global Descriptorsmentioning
confidence: 99%
“…This is the main objective of the so-called conceptual DFT [2,3,4,5,6,7,8,9,10], which gives rise to global and local indicators or descriptors. Among the global indicators one distinguishes the chemical potential [11], chemical hardness [12,13,14], electrophilicity [15,16,17] and nucleophilicity [18,19]. On the other hand local descriptors as the fukui function [20,21,22] f (r ) are able to distinguish the most reactive region in a molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In a formal framework it has allowed introducing in a many empirical chemical concepts like electronegativity [10], hardness [11], so-called reaction force [12], Fukui function [13], electrophilicity [14], electrofugality and nucleofugality [1,2,9,[15][16][17][18], nucleophilicity and solution phase ionization potentials, homofugality [19,20], nucleophilicity [21], among others. In particular, the introduction of concepts like electrophilicity and nucleophilicity to define electron deficient (electrophile) and electron rich (nucleophile) species has gained a continuous interest to construct empirical scales classifying atoms, molecules and charged species [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%